2,9-Bis(trichloromethyl)-1,10-phenanthroline - Fun, Hoong-Kun (International Union of Crystallography, 2010)

(untitled)
The asymmetric unit of the title compound, C(14)H(6)Cl(6)N(2), contains two crystallographically independent molecules, each of which is slightly twisted from planarity. The dihedral angles between the central ring and the two outer rings are 3.81 (7) and 4.30 (7)° in one molecule, and 4.13 (8) and 4.10 (7)° in the other. In the crystal structure, molecules are interlinked by C—Cl⋯Cl interactions into sheets parallel to the ac plane. These sheets are stacked along the b axis in such a way that the molecules are antiparallel; they are further connected into a supramolecular network. There are no classical hydrogen bonds. C⋯Cl [3.637 (2) Å], Cl⋯Cl [3.5639 (5)–3.6807 (8) Å] and Cl⋯N [3.3802 (15)–3.4093 (15) Å] short contacts and π–π interactions, with centroid–centroid distances in the range 3.5868 (9)–3.7844 (9) Å, are observed.